The associations between initial radiographic findings and interventions for renal hemorrhage after high-grade renal trauma: Results from the Multi-Institutional Genitourinary Trauma Study. Issue 6 (June 2019) - Keihani, Sorena; Putbrese, Bryn E.; Rogers, Douglas M.; Zhang, Chong; Nirula, Raminder; Luo-Owen, Xian; Mukherjee, Kaushik; Morris, Bradley J.; Majercik, Sarah; Piotrowski, Joshua; Dodgion, Christopher M.; Schwartz, Ian; et al.
Abstract : BACKGROUND: Indications for intervention after high-grade renal trauma (HGRT) remain poorly defined. Certain radiographic findings can be used to guide the management of HGRT. We aimed to assess the associations between initial radiographic findings and interventions for hemorrhage after HGRT and to determine hematoma and laceration sizes predicting interventions. METHODS: The Genitourinary Trauma Study is a multicenter study including HGRT patients from 14 Level I trauma centers from 2014 to 2017. Admission computed tomography scans were categorized based on multiple variables, including vascular contrast extravasation (VCE), hematoma rim distance (HRD), and size of the deepest laceration. Renal bleeding interventions included angioembolization, surgical packing, renorrhaphy, partial nephrectomy, and nephrectomy. Mixed-effect Poisson regression was used to assess the associations. Receiver operating characteristic analysis was used to define optimal cutoffs for HRD and laceration size. RESULTS: In the 326 patients, injury mechanism was blunt in 81%. Forty-seven (14%) patients underwent 51 bleeding interventions, including 19 renal angioembolizations, 16 nephrectomies, and 16 other procedures. In univariable analysis, presence of VCE was associated with a 5.9-fold increase in risk of interventions, and each centimeter increase in HRD was associated with 30% increase in risk of bleeding interventions. An HRD of 3.5 cm or greater and renal laceration depth of 2.5 cm or greater were most predictive of interventions. In multivariable models, VCE and HRD were significantly associated with bleeding interventions. CONCLUSION: Our findings support the importance of certain radiographic findings in prediction of bleeding interventions after HGRT. These factors can be used as adjuncts to renal injury grading to guide clinical decision making. LEVEL OF EVIDENCE: Prognostic and Epidemiological Study, Level III and Therapeutic/Care Management, Level IV. Abstract : Supplemental digital content is available in the text.